Dramatic Therapeutic Response to Dabrafenib Plus Trametinib in BRAF V600E Mutated Papillary Craniopharyngiomas: A Case Report and Literature Review - Fasano, Morena; Della Corte, Carminia Maria; Caterino, Marianna; Pirozzi, Mario; Rauso, Raffaele; Troiani, Teresa; Martini, Giulia; Napolitano, Stefania; Morgillo, Floriana; Ciardiello, Fortunato (Frontiers in Medicine, 2022)
Background: Craniopharingioma is a rare intracranial tumor, with high morbidity rate due to its common refractiveness to conventional treatments. BRAF V600E has recently been identified as the principal oncogenic molecular driver of papillary craniopharingiomas (PCP), one of the two main variants of craniopharingioma. Case Presentation: a 49 year old man with recurrent craniopharyngioma, harbouring BRAF V600E mutation, has been treated with targeted therapy based on combination of a BRAF-inhibitor, dabrafenib (150 mg, orally twice daily) and a MEK-inhibitor, trametinib (2mg, orally twice daily). Before starting treatment, the patient was symptomatic: he lamented confusion, dysphasia, intense fatigue, that did not allow him to work normally. After just one cycle of treatment, the patient showed an important clinical improvement reporting a progressive regression of the basal symptoms, suggetsing a rapid and dramatic response, then confirmed at first radiological assessment. Thus, treatment was continued and at the time of writing, the treatment is still ongoing (total duration of treatment: 14months) and it is well tolerated, with very good quality of life: patient has no limitation in daily activities and he has even been able to restart to work. Conclusion: The use of target therapies - as a clinical practice or in clinical trials - represents an important therapeutic alternative and a great evolution for patients’ prognosis versus the standard of care, historically represented by unselected chemo-therapies. The discovery of BRAF V600E mutation in patients with PCP is very rare, resulting in lack of data on the efficacy of combination of dabrafenib and trametinib.